Corn arabinoxylan has a repeating structure of subunits of high branch complexity with slow gut microbiota fermentation. (1st August 2022) - Xu, Haidi; Reuhs, Bradley L.; Cantu-Jungles, Thaisa M.; Tuncil, Yunus E.; Kaur, Amandeep; Terekhov, Anton; Martens, Eric C.; Hamaker, Bruce R.
Abstract: Corn arabinoxylan (CAX), a cell wall-derived dietary fiber, was extracted with alkali, partially purified, and treated with hydrolytic enzymes in order to investigate the relationship of fine structure and fermentability by the human gut microbiota. Glycosyl composition and linkage analysis of CAX and two hydrolysates, coupled with molecular size analysis, indicated an organized structural feature of the native polymer, which consists of a repeating structural subunit containing complex branching patterns along the xylan backbone and flanked by regions of less complexity. The two lengths of the highly branched subunit were isolated and were shown to have enhanced slow fermentation property compared to the native structure (3.3 vs. 5.9 mL gas, 4 h), that was related to increasing complexity of the branched structures. Lower molecular size structures with higher branch complexity fermented slower, contrary to a conventional view that small fiber structures approaching the oligosaccharide level are necessarily more rapidly fermented. Graphical abstract: Corn bran arabinoxylan has a repeating subunit fine structure of high branch complexity that relate to its slow gut microbiota fermentation property. Unlabelled Image